Peran Kompleksitas Perusahaan, Audit Internal, Risiko Audit dan Ukuran Dewan Komisaris terhadap Fee Audit Eksternal - Mundiroh, Mundiroh; Khikmah, Siti Noor (Universitas Muhammadiyah Magelang, 2021)
This research aims was to analyse the effect of the company's complexity, internal audit, audit risk and board size on external audit fees. The selection of samples on this study was conducted using purposive sampling methods and obtained 75 samples. Multiple linear regression analysis was used in this research. The results of this study showed that a complexity of the company, audit risk and board size have positive effect on the external audit fee. The internal audit has negative affect on the external audit fee.